2021 IEEE Frontiers in Education Conference (FIE) 2021
DOI: 10.1109/fie49875.2021.9637367
|View full text |Cite
|
Sign up to set email alerts
|

Novice Programming Students' Reflections on Study Motivation during COVID-19 Pandemic

Abstract: In this Research Full Paper, the aim was to explore students' perceptions of their study motivation during COVID-19 pandemic. The goal was to dig into this current topic when it is still fresh. This type of event could be recurring in time and it may also be related to more permanent changes in education. The context of the study was an introductory programming course run in synchronous hybrid mode during COVID-19 pandemic. This was a qualitative study where students were interviewed about study motivation, ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Lohiniva et al [40] conducted a qualitative interview study of novice programming students' experiences studying during the pandemic, focusing on factors impacting motivation. They found that students experienced lower levels of motivation to study resulting from pandemic worries and lack of time, and also difficulties in coordinating collaboration.…”
Section: Experiences Of Virtual Learning 51 Prior Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Lohiniva et al [40] conducted a qualitative interview study of novice programming students' experiences studying during the pandemic, focusing on factors impacting motivation. They found that students experienced lower levels of motivation to study resulting from pandemic worries and lack of time, and also difficulties in coordinating collaboration.…”
Section: Experiences Of Virtual Learning 51 Prior Workmentioning
confidence: 99%
“…Instructor support is vital for students' learning, and that was especially true during the pandemic. Lohiniva et al [40] showed that students in an introductory programming course found it imperative to receive feedback, help and encouragement from the instructor.…”
Section: Study Skills and Supports 71 Prior Workmentioning
confidence: 99%
See 3 more Smart Citations